TELEHEALTH SEBAGAI UPAYA PENINGKATAN KEPUASAN PASIEN DALAM MEMANFAATKAN PELAYANAN KESEHATAN : META ANALISIS - Kurniawan, Hendra Dwi (Jurnal Kesehatan Holistic, 2024)
Introduction : Patient satisfaction is one of the things that all health service providers need to pay attention to. With a high level of satisfaction, it is hoped that it can increase public confidence in the field of health services, so that people do not hesitate to use it. The era of digitalization has had a broad impact on the health sector, one of which is the emergence of telehealth service facilities. Many health service providers have implemented telehealth service facilities to provide the health services needed by patients. It is hoped that the existence of telehealth services can help patients' needs in utilizing the health services they need, so that the level of public health can improve. Objective : to analyze the effectiveness of telehealth services in increasing patient satisfaction in utilizing health services. Method : This research is a meta-analysis and systematic review research with PICO (Population = patients who use telehealth, Intervention = telehealth, Comparison = without using telehealth, Outcome = patient satisfaction). The articles used in this research were obtained from several databases including PubMed, Springer Link, ScienceDirect, and Google Scholar. The articles used are full-text articles from 2019 to 2024. Articles were selected using the PRISMA flow diagram. Articles were analyzed using the RevMan 5.3 application. Results : A total of 7 analyzed articles reviewed in this meta-analysis study came from America, Ethiopia, Iran, and Canada. The study shows that telehealth services can increase patient satisfaction in utilizing health services (aOR 1.51; 95% CI = 1.07 to 1.24; p = 0.01). Conclusion : Patients who use telehealth services in utilizing health service facilities can increase patient satisfaction by 1.51 times compared to patients who do not use telehealth. Keywords: Health services, patient satisfaction, telehealth